The discovery and development of boceprevir. (November 2013) - Rotella, David P
<x xml:space="preserve">Abstract</x> Introduction: Boceprevir was the first direct acting agent developed for the treatment of hepatitis C virus infection. Boceprevir functions by targeting NS3 protease, a viral enzyme essential for replication. This peptidomimetic molecule was optimized from a peptide lead to provide a potent, selective and orally bioavailable drug that can be combined with ribavirin and peg interferon to achieve sustained viral response (undetectable HCV RNA levels for 24 weeks after completion of therapy) in patients infected with Genotype 1 of the virus. Areas covered: This article provides a review of the pre-clinical and clinical discovery of boceprevir. This review includes the role and function of its molecular target, NS3 protease, as well as the assays used to measure in vitro efficacy, compound optimization and clinical studies to demonstrate safety and efficacy. Expert opinion: As the first direct acting anti-HCV agent, boceprevir represents an important advance in therapy of this widespread chronic disease. Yet, while this therapy is a valuable approach, it does have limitations. Studies have suggested that 30% of patients do not achieve sustained viral response and 11% of patients have developed anemia and/or neutropenia. Current drug discovery and development efforts are underway to develop novel therapeutic options that address these issues.